Do Malaysian motorcyclists concern to safety helmet usage: a cross-sectional survey - Ambak, Kamarudin; Ismail, Rozmi; Rahmat, Riza Atiq Ok; Shokri, Foad (Asian Network for Scientific Information (ANSINET), 2011)
The study was carried out to examine percentage of compliance rate regarding helmet used and to identify their characteristics. An observational method and a questionnaire survey were conducted among a group of motorcyclists in Selangor, Malaysia. The observations of 1150 motorcyclists show that only 46.6% used helmets properly, 10.6% untied helmet and 42.8% without-helmet. A random of 300 respondents those improper wearing helmet (either untied helmet or unhelmeted) were interviewed and asked to fill-up a questionnaire. The findings were discussed on background, motorcycling experience, knowledge and attitude of the respondents in details. The percentage of improper helmet usage in the locations of study was considered high and it seem those helmet initiative programs are insufficient to overcome the problem. Also, the characteristics of motorcyclist who did not wearing helmet properly (either unfastened or not wearing helmet) were identified. Therefore, there is need to introduce a new mechanism or method that can be utilized to incorporate behavior adaptation toward safety concern among motorcycle users. Finally, the direction of this study was explained in section of future work.